(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
The word "Siddha" comes from the root word "Citti," which denotes accomplishment, attainment of perfection, and eternal bliss. A scientific and comprehensive approach is used by the Siddha system of medicine, a traditional medical system, to provide preventive, promotional, curative, rejuvenating, and rehabilitative healthcare. At least three loose, liquid, or watery bowel motions per day-also spelt diarrhea- is the definition of diarrhoea. It frequently lasts a few days and can lead to dehydration from fluid loss. The aim of this review article is to explore the scientific literary evidence for the therapeutic usage of Kariveppilai vadagam for Kazhichal/Diarrhoea as mentioned in Citta Vaittiya Tirattu and to concentrate on the Pharmacological activity for the drug’s therapeutic properties. The majority of the raw ingredients used to make Kariveppilai vadagam contain anti-diarrheal activity, which supports its use in diarrhoea.